Telehealth Relaxation, Is It Really Can Decrease The Level Of Anxiety For Pregnant Women During The Pandemic COVID-19? - Purnamaningrum, Yuliasti Eka; Kusmiyati, Yuni; Sumarni, Sri; Petphong, Vajee (Poltekkes Kemenkes Yogyakarta, 2023)
Fetal weight has a very important meaning for planning midwifery care. Deviations found can be corrected immediately both during pregnancy and childbirth so that treatment is carried out on time. Clinical decisions made include the choice of type of delivery. This is expected to improve pregnancy outcomes for the welfare of the mother and fetus. The purpose of this study was to determine the difference in estimated fetal weight using the Insler Formula and the Johnson Formula compared to the baby's birth weight. This study used a cross sectional design. Sample taken by consecutive sampling. The criteria selected were third trimester pregnant women > 37-42 weeks pregnant, do a pregnancy check until giving birth at the Garuda and Ibrahim Aji Public Health Centers in Bandung City from July to November 2022. Estimated fetal weight was measured during antenatal checks using the Insler and Johnson formulas. The estimated fetal weight is compared with the actual weight of the newborn. Based on the results of a study that compared the estimated fetal weight with the baby's birth weight, it was found that there was no significant difference between the use of the Insler and Johnson formulas to measure the estimated fetal weight and birth weight p value > 0.05. The Johnson and Insler formula can be applied by student midwives or midwife practitioners when conducting antenatal care in the third trimester (gestational age > 37-42 weeks). This formula is a simple detection method, using simple tools, easy to obtain and can be used anytime and anywhere, namely a measuring tape. In addition, the measurement guidelines and calculation formulas are simple and easy to apply.